ПРАВОВІ ГАРАНТІЇ ЗАБЕЗПЕЧЕННЯ ПРАВ ПОЛІЦЕЙСЬКИХ В АСПЕКТІ ОТРИМАННЯ ПРАВОВОГО СТАТУСУ УЧАСНИКА БОЙОВИХ ДІЙ - Сіротов, О. А. (Вісник Пенітенціарної асоціації України, 2025)
The general etymological and legal approach to the definition of the term "guarantees" is established. A detailed analysis of the scientific literature is conducted and the main scientific approaches to the content and essence of legal guarantees are identified. Attention is drawn to the existing classifications of legal guarantees. A new, author's definition of legal guarantees for ensuring the rights of police officers in terms of obtaining the legal status of a participant in hostilities is presented. It is proposed that legal guarantees for ensuring the rights of police officers in terms of obtaining the legal status of a participant in hostilities are understood as the conditions, means and principles defined by the Constitution and legislation of Ukraine, the existence of which ensures the implementation and protection of the rights of police officers within the framework of the procedure for obtaining the status of a participant in hostilities. It is stated that these guarantees in the modern conditions of development of national legislation include four key groups of measures, conditions and principles for obtaining the status of a UBD. In particular, it is indicated that legal guarantees for ensuring the rights of police officers in terms of obtaining the legal status of a participant in hostilities in the modern conditions of development of national legislation include: 1) constitutional guarantees; 2) extension to employees of the National Police of the provisions of the special Law of Ukraine dated 22.10.1993 No. 3551-ХІІ; 3) procedural and legal guarantees for obtaining the status of a UBD are unified; 4) special departmental guarantees. Each classification type of guarantees is analyzed.